A Study On Utilisation Of Health Services In A Muslim Slum Community Of Calcutta - Bhattacharya S.K; Bhadra U.K; Nandy S; Ghosh M.M (Wolters Kluwer Medknow Publications, 1991)
A cross- sectional survey of utilization of child immunization and family planning services was carried out in a systematic random sample of 100 families from a Muslim slum community of Calcutta. 15.6% of children (1-4 years) were fully immunized (DPT, OPV & BCG). Couple protection rate was 28.4%. But interestingly, the proportion of protected eligible couples in single families (32.8%) was significantly higher than in joint families (11.6%).